Emerging Security Challenges due to Bring Your Own Device Adoption - Ounza, Jairus E; Liyala, Samuel; Ogara, Solomon (International Journal of Science and Research (IJSR), 2018)
Although a number of researches have been carried out by various organizations across the globe to establish security challenges facing education institutions due to BYOD adoption there is no evidence that a similar study has been carried out for universities in Kenya. Since it is evident that security challenges due to Bring Your Own Device (BYOD) adoption differ across institutions there is need for security challenges facing universities in Kenya due to BYOD adoption to be identified. The study surveyed public and private universities in Kenya in order to investigate security challenges facing them due to BYOD adoption with a view of generating empirical data to enhance their preparedness towards addressing BYOD security challenges. Based on the findings of the study, it was established that BYOD adoption exposes the universities to: lack of control of user devices, lack of user awareness on emerging threats due to user owned devices, difficulties in maintaining inventories of multi-platform user owned devices and increased risk to organizational data. The study recommends that organisations implementing BYOD should continuously establish the security challenges they face as a result of adopting BYOD so as to put in place appropriate security measures to mitigate the challenges.
A Survey of Universities in Kenya
Keywords: Adoption; BYOD; Inventory; Organizational Data; Risk; Security Challenges